2019
DOI: 10.3390/w11122596
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Runoff and Soil Erosion on Abandoned Steep Vineyards in the Mosel Area, Germany

Abstract: The Mosel Wine region has suffered during the last decades a decrease in productive area, mostly on steep sloping vineyards. To avoid the spread of diseases, the extraction of grapevines on abandoned vineyards is mandatory in Rhineland-Palatinate. At the same time, the organic production of wine is growing slowly, but well established in the area. We assess in this paper the degree of the land-use changes, as well as their effect on runoff generation and sediment production, depending on the age of the abandon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…The results of this study indicated that the cultivated lands have a lower content compared to the natural land cover types. These results are in line with other studies elsewhere, indicating that cultivation usually markedly decreases soil carbon [67][68][69][72][73][74]. The forest conversion to cultivation land and settlement (Table 3) likely influences the level of organic carbon due to soil loss, and the more rapid oxidation process of SOC leads to rapid reductions in the SOM values of surface soils [75].…”
Section: Soil Organic Matter On Soil Aggregate Stability In Different...supporting
confidence: 90%
“…The results of this study indicated that the cultivated lands have a lower content compared to the natural land cover types. These results are in line with other studies elsewhere, indicating that cultivation usually markedly decreases soil carbon [67][68][69][72][73][74]. The forest conversion to cultivation land and settlement (Table 3) likely influences the level of organic carbon due to soil loss, and the more rapid oxidation process of SOC leads to rapid reductions in the SOM values of surface soils [75].…”
Section: Soil Organic Matter On Soil Aggregate Stability In Different...supporting
confidence: 90%
“…Land use change, abandonment and the conversion of natural ecosystems to cultivated lands has an impact on the distribution of SOC in the various size fractions of aggregates, this has already been studied in various soils and diverse climatic conditions (Bronick and Lal, 2005;Helfrich et al, 2006;Hoyos andComerford, 2005, Cerdà et al, 2018;Seeger et al, 2019). However, few studies have been conducted concerning the effects of land use change on SOC pools and soil aggregate size fractions in the vulnerable ecosystem of Hyrcanian forest soils in north of Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Erosion might increase in dry regions, where vegetation recovery is low or interrupted by wildfires (García‐Ruiz & Lana‐Renault, 2011; Rodrigo‐comino et al, 2018). For example, the transition from initially higher erosion rates following abandonment to lower rates following vegetation recovery has been observed in Eastern Spain (Cerdà et al, 2018) and Germany (Seeger et al, 2019). Decreased erosion rates were observed in vineyards in Northern Italy (Sciubba et al, 2021) and central (Quintana et al, 2021) and northeastern Spain (Dunjó et al, 2003) following abandonment.…”
Section: Discussionmentioning
confidence: 96%
“…Vineyards are one of the most erosion‐prone types of cultivated land in Europe (Biddoccu et al, 2020; Cerdan et al, 2010; Rodrigo‐Comino, 2018), including the Mediterranean region (García‐Ruiz et al, 2013; Prosdocimi et al, 2016), central Europe (Burg et al, 2018; Szilassi et al, 2006), and Slovakia (Cebecauer & Hofierka, 2008; Šúri et al, 2002) due to the combination of fragile or bare soils, steep slopes, and cultivation practices (García‐Ruiz, 2010; Rodrigo Comino et al, 2017). At the same time, the vineyards in particular regions are threatened by abandonment (Cossart et al, 2020; Foronda‐Robles, 2018; Incze & Novák, 2016; Seeger et al, 2019). The area of vineyards in Slovakia has dramatically decreased over the last 30 years (Lieskovský et al, 2013; Slámová & Belčáková, 2020).…”
Section: Introductionmentioning
confidence: 99%